KOLABORASI MENINGKATKAN KEWIRAUSAHAAN PEREMPUAN DALAM SEKTOR INDUSTRI PAKAIAN DI WILAYAH GUNUNG KIDUL - Sahmi Afandi, Titis Tatasari, Arinndah Cindy, Divani Sesillia (Perkumpulan Dosen Program Hibah Indonesia, 2025)
Women's entrepreneurship in the Gunung Kidul region has great potential to contribute to the local economy, especially in the clothing industry sector. This study aims to analyze the role of collaboration in improving women's entrepreneurship in the region. The research method used is a qualitative approach with case studies on several women business actors in the clothing industry. The results show that collaboration with various stakeholders, such as governments, the private sector, educational institutions, and local communities, can provide significant support in the form of access to capital, training, and business network development. This collaboration also encourages innovation and increases business productivity. In conclusion, multi-sector collaboration is very important in supporting the success of women's entrepreneurship in the clothing industry sector in Gunung Kidul, and has positive implications for improving the economy and welfare of the local community.Keyword: collaboration, women